Fenomena Labeling Kafir dan Sesat terhadap Komunitas Jemaat Ahmadiyah dan Pengaruhnya dalam Kehidupan Sosial Para Anggotanya - Javier Ikram Wiradinata; Elly Esra Kudubun; Antik Tri Susanti (Yayasan Literasi Sains Indonesia, 2025)
This study examines the phenomenon of labeling the Indonesian Ahmadiyya Community (JAI) as ‘infidel’ (kafir) and ‘heretical’ (sesat) and its profound influence on the social lives of its members. Using a qualitative approach that combines observation, in-depth interviews, and a literature review, analyzed through the framework of Labeling Theory, this research reveals how the stigma is not just a product of theological differences but is socially constructed and institutionalized through religious fatwas and state policies like the Joint Ministerial Decree (SKB 3 Menteri). This process effectively transforms differences in belief into a justification for systemic and widespread persecution. The findings indicate that the impacts of this labeling are multidimensional, ranging from brutal physical violence, such as in the Cikeusik tragedy and the destruction of mosques, to systemic discrimination that hinders access to public services and civil rights. Furthermore, the psychosocial consequences are significant, creating collective trauma, fear, and deep social isolation, with children being the most vulnerable victims. Amidst this wave of rejection, the Ahmadiyya community demonstrates resilience by developing a dual adaptation strategy: strengthening internal solidarity while adopting an accommodative external approach through positive social participation and a firm commitment to the principle of non-violence. This research concludes that the ‘heretical’ label has functioned as a master status that fundamentally shapes, limits, and defines the social reality of the Ahmadiyya community in Indonesia.